The CRISPR-Cas toolbox and gene editing technologies - Liu, Guanwen; Lin, Qiupeng; Jin, Shuai; Gao, Caixia (Molecular cell, 2022)
The emergence of CRISPR-Cas systems has accelerated the development of gene editing technologies, which are widely used in the life sciences. To improve the performance of these systems, workers have engineered and developed a variety of CRISPR-Cas tools with a broader range of targets, higher efficiency and specificity, and greater precision. Moreover, CRISPR-Cas-related technologies have also been expanded beyond making cuts in DNA by introducing functional elements that permit precise gene modification, control gene expression, make epigenetic changes, and so on. In this review, we introduce and summarize the characteristics and applications of different types of CRISPR-Cas tools. We discuss certain limitations of current approaches and future prospects for optimizing CRISPR-Cas systems.